1995
DOI: 10.1038/nsb1295-1131
|View full text |Cite
|
Sign up to set email alerts
|

A paradigm for drug discovery using a conformation from the crystal structure of a presentation scaffold

Abstract: We describe a structural validation of the use of presentation scaffolds for control and elucidation of bioactive conformations of peptides. The protein REI-RGD34--produced by inserting the sequence RIPRGDMP into the CDR1 loop region of the immunoglobulin VL domain REI--strongly inhibits fibrinogen binding to the integrins alpha IIb beta 3 and alpha V beta 3. In the X-ray crystal structure of their protein at 2.4 A resolution, the RGD-containing loop exhibits defined electron density that is consistent with mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…However, bacterial cell surface display or mRNA display might also have been successful as these technologies have previously been used to present folded EETI-II variants for high-throughput screening. 29,33,43 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, bacterial cell surface display or mRNA display might also have been successful as these technologies have previously been used to present folded EETI-II variants for high-throughput screening. 29,33,43 …”
Section: Discussionmentioning
confidence: 99%
“…32,43,49,50 However, in some cases these studies did not generate proteins with sufficient integrin binding affinities or biological activities for therapeutic applications, 32,50 presumably because simple loop grafting did not result in optimal presentation of residues within the RGD-containing loop to integrin receptors. When high affinity was achieved, the ligand was shown to bind promiscuously to α v β 3 and α iib β 3 integrins.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacophoric activity can be expected from the RGD ligand towards the platelet receptor α IIb β 3 only when the distances R C α ‐D C α and R C β ‐D C β are ≥ 0.7 nm and 1.0 nm, respectively . In our study, the peptides RGD and PRGD showed the sampling of two conformations, that is extended and compact, irrespective of the temperature variation.…”
Section: Discussionmentioning
confidence: 48%
“…Only the monomeric form of this Ig fragment was shown to be active and to recognize an antigen expressed by human cells of the melanocytic lineage. In an approach to controlling and elucidating bioactive conformations of peptides, the dimeric Ig V L domain REI was successfully utilized as a presentation scaffold (Zhao et al, 1995). In an approach to controlling and elucidating bioactive conformations of peptides, the dimeric Ig V L domain REI was successfully utilized as a presentation scaffold (Zhao et al, 1995).…”
Section: Single Ig and Ig-like Domainsmentioning
confidence: 99%